2020
DOI: 10.3390/cancers12113348
|View full text |Cite
|
Sign up to set email alerts
|

Severe Salmonella spp. or Campylobacter spp. Infection and the Risk of Biliary Tract Cancer: A Population-Based Study

Abstract: Salmonella spp. infection has shown to have oncogenic transformative effects and thereby increases the risk of certain cancers. For Campylobacter spp., similar effects have been demonstrated. Risk factor identification may allow for timely diagnosis and preventive treatment. To substantiate the oncogenic potential of Salmonella and Campylobacter spp., this study compared the incidence of extrahepatic biliary tract cancer (BTC) in patients with diagnosed Salmonella or Campylobacter spp. infection with BTC incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…CDT causes double-stranded DNA breaks that may contribute to cancer formation ( He et al, 2019 ). In Supplementary Table 4 nine epidemiological studies are summarized which assess the association between Campylobacter and GI cancer ( Brauner et al, 2010 ; Blackett et al, 2013 ; Wu et al, 2013 ; Allali et al, 2015 ; Alexander et al, 2016 ; Mughini Gras, 2017 ; De Savornin Lohman et al, 2020 ; Wang et al, 2020 ; Wei et al, 2020 ). In humans, Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CDT causes double-stranded DNA breaks that may contribute to cancer formation ( He et al, 2019 ). In Supplementary Table 4 nine epidemiological studies are summarized which assess the association between Campylobacter and GI cancer ( Brauner et al, 2010 ; Blackett et al, 2013 ; Wu et al, 2013 ; Allali et al, 2015 ; Alexander et al, 2016 ; Mughini Gras, 2017 ; De Savornin Lohman et al, 2020 ; Wang et al, 2020 ; Wei et al, 2020 ). In humans, Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…Three cohort studies assessed the association between Campylobacter infection and risk of colon cancer (CC), biliary tract cancer or multiple types of cancer later in life. All three studies used a follow-up time of more than 10 years ( Supplementary Table 4 ; Brauner et al, 2010 ; Mughini Gras, 2017 ; De Savornin Lohman et al, 2020 ). None of the studies found a significantly increased risk of digestive cancer after infection compared to the general population, all with standardized incidence ratios (SIRs) below or close to 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied in the context of association with oncological diseases is the intestinal microbiota. [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%